The Dominant Role of Foreign Direct Investment in Shaping Carbon Emissions and Deforestation in Singapore - Dodi Tirtana; Galih Nugraha; Dim Zarita Suryanugraha (Jurnal Ekonomi Pembangunan, 2025)
Climate change and environmental degradation are linked to carbon emissions (CO₂), foreign direct investment (FDI), and deforestation, which are central to sustainable development research. This study analyzes their relationship from 2001 to 2023 using the Vector Error Correction Model (VECM). The Augmented Dickey-Fuller and Johansen tests confirm that all variables are integrated of order one (I(1)) and share a long-term equilibrium relationship, thereby justifying the model choice. Results show that deforestation significantly reduces carbon emissions in the long run, while FDI has a positive but marginal effect. In the short run, only deforestation adjusts to restore balance. Diagnostic tests confirm model stability and reliability. Granger causality reveals that FDI drives deforestation, while emissions and FDI jointly influence it. The Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) show that carbon emissions are mainly self-driven, while FDI and emissions increasingly shape deforestation. These findings highlight the need for integrated economic–environmental policies.